SEASONAL ABUNDANCE OF LARVAE AND POST-LARVAE OF THE COMMERCIALLY IMPORTANT PENAEID PRAWNS IN THE INSHORE WATERS OF COCHIN - Rao, P Vedavyasa (Indian Journal of Fisheries, 2011)
Seasonal distribution of the larvae and post-larvae of five species of the commercially important penaeid prawns of the Cochin area during the years 1966- 67, 1967-68 and 1968-69 showed that the larvae and post-larvas of Metapenaeus dobsoni form;d a major component (80%) of the total larval population in the inshore waters. The larvae and post-larvae of Parapenaeopsis stylifera were next in the order of abundance. The annual fluctuations in the occurrence of the larvae and post-larvae of Metapenaeus monoceros, M. affinis and Penaeus indicus were very wide. The percentage reduction in the total number, from larvae to post-larvae, which was attributed as mortality rate, varied from year to year in different species. Most of these species breed throughout the year with two peak’si one during October-December which is common to all the species and thj other which is less pronounced extends from May to August. The larvae of most of the species are able to withstand a wide range in salinity. The larvae of P. stylifera are generally absent in the inshore waters during the monsoon months. A greater abundance of the larvae in the inshore waters during the year seems to indicate a good prawn fishery in the subsequent season.